Diffractive multifocal intraocular lens interferes with intraoperative view - Mami Yoshino; Makoto Inoue; Nae Kitamura; et al (Clinical Ophthalmology, 2010)
Mami Yoshino1, Makoto Inoue1,2, Nae Kitamura1, Hiroko Bissen-Miyajima11Department of Ophthalmology, Tokyo Dental College Suidobashi Hospital, Tokyo, Japan; 2Kyorin Eye Center, Kyorin University School of Medicine, Tokyo, JapanAbstract: We report an unusual finding during vitreous surgery in an eye implanted with a diffractive multifocal intraocular lens (IOL). A 70-year-old woman reported gradual visual deterioration to 20/40 in the left eye two and a half years after uneventful cataract surgery with implantation of a diffractive multifocal IOL. Funduscopic examination showed an epiretinal membrane (ERM) in the left eye. Increased macular traction was believed to cause the visual deterioration. Vitreous surgery with removal of the ERM was performed and triamcinolone acetonide (TA) was injected intravitreally to visualize the residual vitreous cortex. Although the ERM was peeled successfully, the ability to focus on the vitreoretinal interface through the IOL required great effort with decreased contrast sensitivity and ghost images of the intravitreal TA crystals. The vision improved to 20/25 4 months postoperatively. Macular surgery can be performed in an eye with a diffractive multifocal IOL; however, decreased contrast sensitivity and ghost images may interfere with the intraoperative view through the diffractive IOL in complicated cases.Keywords: diffractive multifocal intraocular lens, intraoperative view